PERANCANGAN APLIKASI DESKTOP KASIR PADA BENGKEL MOTOR DI SURABAYA - Louis Maximillian; Ivan Sanjaya; Edwin Alexander (Universitas Muhammadiyah Gresik, 2024)
Workshops are a business that has an important role in the Indonesian economy. However, there are still many workshops that do not have a good operational system, especially in terms of recording transactions. This can cause the workshop to be less efficient and effective in running its business. In this research, the author developed a desktop cashier application for workshops. This application was built using Python, PyQt5, and MySQL. This application has features that can help workshops in recording transactions, such as master data, transactions, reports and settings. The research results show that this desktop cashier application can help workshops improve their operational efficiency and effectiveness. This application can make it easier for workshops to record transactions, produce accurate reports, and manage workshop data.